Potential of Crypto Assets as Loan Collateral in Indonesia - Ade Rizki Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research reviews the potential for using crypto assets as loan collateral in Indonesia. By focusing on regulatory aspects, risks, benefits and stakeholder perceptions, this research analyzes how crypto assets can be used as collateral in loan transactions. A mixed methodology was used to gain a holistic understanding, encompassing both qualitative and quantitative analysis. The results highlight the legal complexities, protections, and need for more comprehensive regulations in facilitating the use of crypto assets as loan collateral in Indonesia